2022
DOI: 10.47391/jpma.3249
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of early weaning and non-nutritive sucking habits with facial development

Abstract: Objective: To determine the frequency of malocclusion features, convex facial profile and non-nutritive sucking habits among children with and without early weaning. Methods: The cross-sectional study was conducted at the National Institute of Child Health, Karachi, from June to December 2020, and comprised of either gender aged 3-6 years. The subjects were clinically examined, and details of lactation period, bottle feeding, thumb and pacifiers sucking were gathered from the parents to assess association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…These interferences can lead to the establishment of malocclusions [34]. Studies have shown associations between pacifier use and the development of anterior open bite and posterior crossbite [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These interferences can lead to the establishment of malocclusions [34]. Studies have shown associations between pacifier use and the development of anterior open bite and posterior crossbite [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…This nonnutritive sucking habit can exert a negative impact on the tone of muscles involved in chewing and compromise normal swallowing dynamics [38]. Moreover, anterior open bite, which is found with greater frequency in patients who use a pacifier [14], may also be an etiological factor in the development of atypical swallowing, as swallowing dynamics are compromised in such cases due to lingual interposition and the absence of lip seal [39]. One pediatric dentistry association and one pediatric association reported the occurrence of mouth breathing in patients who use a pacifier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen cross-sectional studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35] and seven cohorts [36][37][38][39][40][41][42][43][44][45][46][47] were identified. These studies were conducted in Brazil [23,24,27,30,33,35,[39][40][41][42], China [22,25,32], USA [36,38], India [26], Slovenia [28], Senegal [29], Puerto Rico [31] and Spain [34].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Breastfeeding is defined as one of the foundations of health promotion and the prevention of many diseases and is one of the pillars of correct maxillofacial growth because it favors proper lip sealing, jaw function and the position of the tongue against the palate [43]. Indeed, breastfeeding forces the child to actively extract milk from the mother's breast through the synergistic action of the tongue and facial muscles [7,[44][45][46][47][48]. In opposition, bottle feeding requires less effort to drain the milk, so it does not stimulate the functional matrix and favors the development of malocclusions such as a posterior crossbite, anterior open bite, increased protrusion and a class II molar and canine relationship.…”
Section: Breast-feeding Vs Bottle-feedingmentioning
confidence: 99%